Optimization of alloying element types and contents in high strength and high toughness bainitic steels - Ranran Zhu; Xiaoyan Long; Fucheng Zhang; Zhinan Yang; Yanguo Li; Yan Yang; Yifei Wang (Journal of Materials Research and Technology)
Currently, the high alloy content of bainitic steels imparts excellent properties but also leads to problems such as high cost of production and difficulties in recycling and reuse. This study investigates the optimization of alloying element types and contents in bainitic steels through a continuous cooling heat treatment process of the three tested steels, employing characterization techniques including optical microscopy, scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and electron backscatter diffraction. Results indicate that adjusting alloy ratios allows steel without adding precious elements to achieve comparable properties to those containing precious elements. MnAl–1Si and MnSi–1Al steels have a very small volume fraction of retained austenite and are predominantly thin-film, which improves their impact toughness and reduces elongation. Additionally, MnAl–1Si steel shows thinner laths thickness and higher dislocation density, so its strength is increased. This study suggests that reducing alloy types and amounts presents a viable approach to sustainable manufacturing practices.